2017
DOI: 10.1111/icad.12281
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the species richness of parasitoid wasps (Ichneumonidae: Pimplinae and Rhyssinae) across sites on different continents

Abstract: The old idea that parasitoid wasps (Ichneumonidae) show an inverse latitudinal diversity gradient has recently been challenged, but how ichneumonid species richness varies across the globe is still not well understood. We carried out field inventories in 21 sites on three continents to clarify this question, focusing on the subfamilies Pimplinae and Rhyssinae. Our total sampling effort was 628 Malaise trap months and the total catch exceeded 65 000 individuals. Our main focus was in two intensively inventoried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 52 publications
(58 reference statements)
0
51
2
Order By: Relevance
“…This ranking of absolute numbers is most probably related to the sampling design, since in Sweden the traps were open for seven days, compared to a single day in Brazil and South Africa for logistic reasons. In mega-diverse habitats such as Amazonia, a comprehensive long-term insect diversity sampling may take months or even years and should be carried out with multiple collecting methods (Gómez et al 2018;Matos-Maraví et al 2018). However, in light of logistic and financial limitations, fast massive sampling such as one week or even one day may allow a rather substantial biodiversity registration, especially when compared to a one-day traditional inventory of macroorganisms such as vertebrates or plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ranking of absolute numbers is most probably related to the sampling design, since in Sweden the traps were open for seven days, compared to a single day in Brazil and South Africa for logistic reasons. In mega-diverse habitats such as Amazonia, a comprehensive long-term insect diversity sampling may take months or even years and should be carried out with multiple collecting methods (Gómez et al 2018;Matos-Maraví et al 2018). However, in light of logistic and financial limitations, fast massive sampling such as one week or even one day may allow a rather substantial biodiversity registration, especially when compared to a one-day traditional inventory of macroorganisms such as vertebrates or plants.…”
Section: Discussionmentioning
confidence: 99%
“…Another important advantage of the use of bulk insect samples is that it can be used in a wide range of environments, from hot and humid rainforests, to species-rich Mediterranean meadows, and natural and anthropogenic habitats in the temporal zone. The use of non-destructive DNA extraction also allows complementary taxonomic studies, speeding up the discovery of new species (e.g., Gómez et al 2018). Adopting a massive and standardised sampling scheme would allow fast and cost-effective estimations of global biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…After Hymenoptera, the Coleoptera may not even be the second most-speciose order; several recent inventories of species diversity suggest that the Diptera may hold that title [ 17 , 94 , 95 ]. Moreover, other historically-accepted ideas about diversity of parasitoid hymenopterans have recently been questioned, including the apparent myth that parasitoids are one of only a few groups whose diversity decreases towards the tropics [ 96 98 ]. In any case, we hope this commentary results in a redoubled effort to understand and describe the ecology and natural histories of parasitoid wasps, including host ranges and cryptic host-associated diversity, such that estimates of P:H can be made for additional host genera.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…In addition to these, a one-week intensive "Diptera-Blitz" was conducted by a large network of experts, inspired on the BioBlitz concept (e.g., Lundmark, 2003) which aims at recording most of biodiversity at one locality during a short time period. In another case study, Gómez et al (2018) sampled the Western Amazonian local parasitoid wasp diversity by using 41 Malaise traps in three separate field campaigns and seasons, with a total sampling effort of 230 Malaisetrap months scattered throughout 1998 to 2011 (one Malaise-trap month corresponds to one trap collecting in the field for a period of one month). In this case, despite the massive sampling effort, cumulative species curves suggested that a significant portion of the local parasitoid diversity remained unobserved; a fact that can be generalized for many other tropical insect groups.…”
Section: Rule 3: Go To the Fieldmentioning
confidence: 99%